Beyond Auteurism : New Directions in Authorial Film Practices in France, Italy and Spain since the 1980s. - Maule, Rosanna (Intellect, 2008)
Beyond Auteurism is a comprehensive study of nine film authors from France, Italy and Spain who since the 1980s have blurred the boundaries between art-house and mainstream, and national and transnational film production. Maule examines how the individuals have maintained a dialectical relationship with the authorial tradition of the national cinema to which each belongs. In considering this tradition, Maule seeks to illustrate that the film author is not only the most important symbol of European cinema?s cultural tradition and commitment, but is also a crucial part of Europe?s efforts to dev.